Pearl Tropicana / Azean Omar ... [et al.] - Omar, Azean; Jamil, Emma Hanis; Ramlee, Mellissa; Abd. Rashid, Nur Atikah (Faculty of Office Management & Technology, 2004)
Pearl Tropicana is a partnership company that offers, "Pearl Tropicana fruit jam". We have chosen Pearl Tropicana as our company's name because it refers to tropical fruit that we put in our jam. Where as Pearl is refer to cleanliness and tidiness when we produce our jam. Our jam is also fresh and safe to eat. Our company is listed under IKS which is stand for "Industri Kecil Sederhana". Our product is 100% used local raw material in order to promote our local fruit. We have chosen to operate at No. 16, Jalan Perbahan Satu, 26/2A, Seksyen 26, 40400 Shah Alam, Selangor Darul Ehsan. That will include our factory to produce our jam in ground floor where as the first floor is where our office located. We have choose one lot of 15 X 30 feet shop houses as our operation place.